Determinasi Pengungkapan Key Audit Matters: Perspektif Teori Audit Expectation Gap - Fatkhur Rohman; Widya Rizki Eka Putri; Syaharani Noer Fathia; Ayu Dwiny Octary; Rona Majidah (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to explore the factors influencing the disclosure of Key Audit Matters (KAM) in audit reports, using the Audit Expectation Gap Theory as a theoretical framework. Based on a literature review of 15 articles published between 2020 and 2025, it was found that factors such as company characteristics (size and complexity), auditor characteristics (experience and specialization), and corporate governance significantly influence the quality and quantity of Key Audit Matters disclosure. Larger and more complex companies tend to disclose more Key Audit Matters, while auditors from large firms provide more detailed disclosures. Furthermore, disclosures that are too generic or use overly formal and non-specific language risk exacerbating the expectation gap. Therefore, it is essential for regulators and auditors to continually improve guidelines and evaluate the implementation of Key Audit Matters to meet transparency and accountability goals.